A Verbal Anchor based Fuzzy System to help business managers build Balanced Scorecards Strategy Maps - Ladeira, Marcelo; Linhares, Fernando (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2015.5860, 2015)
The Balanced Scorecard (BSC) methodology was proposed to help companies create simple strategy plans that can be explained to all employees. The core of this tool is the strategy map that shows a collection of strategic objectives a company needs to achieve its mission. Small and medium companies find it difficult to create their own strategies without the help of a management consultant, which is not always affordable. This paper presents the Mistral Solutions, a system that supports entrepreneurs and their teams to create their own BSC initial strategy maps. The system proposed is based on fuzzy logic. Initially the user takes a online survey about his/her enterprise. During the knowledge acquisition a verbal anchor scale can be used to represent numeric information if the entrepreneur does not know the exact values for each question answer. The Mistral Solutions uses the answers to ground fuzzy rules for creating business strategies in the shape of BSC strategy maps. The system proposes eight strategic objectives, two for each of the four classic BSC perspectives. These strategic objectives are chosen from a set of forty-five possibilities. The knowledge base has one-hundred-eleven variables and onehundred-twenty-six fuzzy rules. This system was applied to institutions representing the public sector, the private sector and a public concession. In the empirical evaluation, the system performed better when applied to private sector institution when all the eight strategic objectives were considered adequate by the manager in charge of the strategic planning of this institution.